Organization of the Addax Major Histocompatibility Complex Provides Insights Into Ruminant Evolution - Li, Chaokun; Huang, Rui; Nie, Fangyuan; Li, Jiujie; Zhu, Wen; Shi, Xiaoqian; Guo, Yu; Chen, Yan; Wang, Shiyu; Zhang, Limeng; Chen, Longxin; Li, Runting; et al. (Frontiers in Immunology, 2020)
Ruminants are critical as prey in transferring solar energy fixed by plants into carnivorous species, yet the genetic signature of the driving forces leading to the evolutionary success of the huge number of ruminant species remains largely unknown. Here we report a complete DNA map of the major histocompatibility complex (MHC) of the addax (Addax nasomaculatus) genome by sequencing a total of 47 overlapping BAC clones previously mapped to cover the MHC region. The addax MHC is composed of 3,224,151 nucleotides, harboring a total of 150 coding genes, 50 tRNA genes, and 14 non-coding RNA genes. The organization of addax MHC was found to be highly conserved to those of sheep and cattle, highlighted by a large piece of chromosome inversion that divided the MHC class II into IIa and IIb subregions. It is now highly possible that all of the ruminant species in the family of Bovidae carry the same chromosome inversion in the MHC region, inherited from a common ancestor of ruminants. Phylogenetic analysis indicated that DY, a ruminant-specific gene located at the boundary of the inversion and highly expressed in dendritic cells, was possibly evolved from DQ, with an estimated divergence time ~140 million years ago. Homology modeling showed that the overall predicted structure of addax DY was similar to that of HLA-DQ2. However, the pocket properties of P1, P4, P6, and P9, which were critical for antigen binding in the addax DY, showed certain distinctive features. Structural analysis suggested that the populations of peptide antigens presented by addax DY and HLA-DQ2 were quite diverse, which in theory could serve to promote microbial regulation in the rumen by ruminant species, contributing to enhanced grass utilization ability. In summary, the results of our study helped to enhance our understanding of the MHC evolution and provided additional supportive evidence to our previous hypothesis that an ancient chromosome inversion in the MHC region of the last common ancestor of ruminants may have contributed to the evolutionary success of current ruminants on our planet.